Impact of Milk Powder Imports on Local Milk Industry and Consumers’ Welfare in Sri Lanka - Krishnapillai, Sooriyakumar; Sathiyamoorthy, Sarujan; Sireeranhan, Anushiya (International Journal of Economics and Financial Issues, 2020)
This paper examines the economic effects of milk powder imports on domestic milk industry and consumers’ welfare. Domestic milk production fullfilled around 40 % of the demand in 2016. The generalized inverse demand system model was employed. The result shows that a 10% increase in milk powder imports increases consumers’ welfare by USD 20 million and fresh milk and local milk powder industry will suffer economic losses. Therefore, until domestic producers develop the capacity to compete with international competitors, government should provide subsidies, credit facilities and technical assistance to all dairy farmers, middlemen, milk collecting centers, dairy farmers associations and cooperatives involved in domestic dairy industry. Government should provide assistance and facilities to domestic fresh milk processors to promote fresh milk consumption by non-price competition strategy. Importers of milk products and local milk processors could use this finding to develop their business strategy. Keywords: Consumer welfare; Generalized Inverse Demand System Model; Import of Milk Powder JEL Classifications: Q11, Q17, Q18 DOI: https://doi.org/10.32479/ijefi.10213